Introduction to InfoPath 2007 - Miles, Timothy J.; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course introduces the user to Microsoft InfoPath 2007. In this course you will learn how to create new Form Templates and properly utilize the different controls and their associated properties to assist users. With a strong emphasis on the underlying data structure created by InfoPath and the associated controls, this course gives you everything you needs to create effective and useful Form Templates. You will also learn how to import, export and merge data; protect and publish forms; and work with views."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 9, 2013).
Presenter, Timothy Miles.
Keywords: Microsoft InfoPath; Business -- Forms -- Computer programs; Electronic books